Consensus from European experts on severe eosinophilic asthma and chronic rhinosinusitis with nasal polyps: Results from the OverSEA Delphi study - Claus Bachert, MD, PhD; Guy Brusselle, MD, PhD; José Antonio Castillo Vizuete, MD, PhD; Ignacio Dávila, MD, PhD; Martin Laudien, MD, PhD; Veronica Seccia, MD, PhD; Peter Schmid-Grendelmeier, MD, PhD; Alessandra Vultaggio, MD, PhD; Konstantina Kallinikou, PhD; Laura Walrave, PhD; Ludger Klimek, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Managing patients with severe asthma with an eosinophilic phenotype (SEA) with comorbid respiratory conditions such as chronic rhinosinusitis with nasal polyps (CRSwNP) continues to encounter significant challenges and lack of coordinated management among treating physicians. Objective: The OverSEA study aims to provide insights into current clinical practices and formulate recommendations for managing these patients. Methods: The two-round Delphi survey, conducted March-June 2023, was developed by a multidisciplinary 11-member Scientific Committee including pulmonologists, allergists, and ear, nose and throat specialists, and involved 205 experts from these specialties across 8 European countries. Consensus was defined as ≥70% agreement. Topics covered included the initial assessment, treatment, follow-up, and multidisciplinary management of patients with SEA and CRSwNP. Results: There was a consensus that evaluating for CRSwNP (88%), allergic rhinitis (79%), chronic rhinosinusitis without nasal polyps (77%), and aspirin/nonsteroidal anti-inflammatory-exacerbated respiratory disease (71%) is crucial for diagnosing upper respiratory tract comorbidities in patients with SEA. The necessity of a multidisciplinary approach for all stages of disease management (diagnosis, 82%; treatment decision-making, 83%, follow-up, 79%), and the usefulness of biologics in simultaneously managing asthma and CRSwNP symptoms (87%) were emphasized. Conclusion: The OverSEA study is the largest European initiative providing recommendations for optimizing the management of patients with SEA and comorbid CRSwNP. It underscores the importance of evaluating patients with SEA for comorbid upper airways diseases, particularly CRSwNP, and promotes a multidisciplinary approach, encouraging pulmonologists, allergists, and otorhinolaryngologists to collaborate closely to streamline patient diagnosis, follow-up, and treatment decisions.